Involvement of Conserved Amino Acids in the C-Terminal Region of LINE-1 ORF2p in Retrotransposition - Christian, Claiborne M. (Genetics, 2017)
Long interspersed element 1 (L1) is the only currently active autonomous retroelement in the human genome. Along with the parasitic SVA and short interspersed element Alu, L1 is the source of DNA damage induced by retrotransposition: a copy-and-paste process that has the potential to disrupt gene function and cause human disease. The retrotransposition process is dependent upon the ORF2 protein (ORF2p). However, it is unknown whether most of the protein is important for retrotransposition. In particular, other than the Cys motif, the C terminus of the protein has not been intensely examined in the context of retrotransposition. Using evolutionary analysis and the Alu retrotransposition assay, we sought to identify additional amino acids in the C terminus important for retrotransposition. Here, we demonstrate that Gal4-tagged and untagged C-terminally truncated ORF2p fragments possess residual potential to drive Alu retrotransposition. Using sight-directed mutagenesis we identify that while the Y1180 amino acid is important for ORF2p- and L1-driven Alu retrotransposition, a mutation at this position improves L1 retrotransposition. Even though the mechanism of the contribution of Y1180 to Alu and L1 mobilization remains unknown, experimental evidence rules out its direct involvement in the ability of the ORF2p reverse transcriptase to generate complementary DNA. Additionally, our data support that ORF2p amino acids 1180 and 1250–1262 may be involved in the reported ORF1p-mediated increase in ORF2p-driven Alu retrotransposition.